Murine peripheral NK‐cell populations originate from site‐specific immature NK cells more than from BM‐derived NK cells. Issue 5 (31st March 2016) - Pinhas, Nissim; Sternberg‐Simon, Michal; Chiossone, Laura; Shahaf, Gitit; Walzer, Thierry; Vivier, Eric; Mehr, Ramit
Abstract : Early NK‐cell progenitors mostly differentiate directly into the CD27 + Mac‐1 – subset rather than through the CD27 – Mac‐1 – subset. NK cell exit from the bone marrow is insufficient to supply NK‐cell populations in the spleen or the liver. Thus, liver and spleen NK cells likely develop mostly from tissue‐resident progenitors. Abstract : Murine NK cells can be divided by the expression of two cell surface markers, CD27 and Mac‐1 (a.k.a. CD11b), into four separate subsets. These subsets suggest a linear development model: CD27 – Mac‐1 – → CD27 + Mac‐1 – → CD27 + Mac‐1 + → CD27 – Mac‐1 + . Here, we used a combination of BrdU labeling experiments and mathematical modeling to gain insights regarding NK‐cell development in mouse bone marrow (BM), spleen and liver. The modeling results that best fit the experimental data show that the majority of NK cells already express CD27 upon entering the NK‐cell developmental pathway. Additionally, only a small fraction of NK cells exit the BM to other sites, suggesting that peripheral NK‐cell populations originate from site‐specific immature NK cells more than from BM‐derived mature NK cells.